DETERMINAN KEPATUHAN WAJIB PAJAK: KONDISI KEUANGAN SEBAGAI PEMODERASI: (Studi Empiris Wajib Pajak Badan yang terdaftar di KPP Pratama Jakarta Kebayoran Baru Dua) - Suwanti; Eva Herianti; Sulhendri (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
The tax ratio from 2014 to 2020 did not show any significant development. The Covid-19 pandemic that is currently happening has caused the 2020 tax ratio to decrease to 9.73. The tax ratio can be increased by increasing tax compliance. This study aims to measure